2015
DOI: 10.3389/fpsyg.2015.00821
|View full text |Cite
|
Sign up to set email alerts
|

Neurodynamics of executive control processes in bilinguals: evidence from ERP and source reconstruction analyses

Abstract: The present study was designed to examine the impact of bilingualism on the neuronal activity in different executive control processes namely conflict monitoring, control implementation (i.e., interference suppression and conflict resolution) and overcoming of inhibition. Twenty-two highly proficient but non-balanced successive French–German bilingual adults and 22 monolingual adults performed a combined Stroop/Negative priming task while event-related potential (ERP) were recorded online. The data revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 67 publications
4
44
4
Order By: Relevance
“…However, results are far from consensual and several studies reported a clear bilingual advantage for performing various tasks involving executive control (e.g. Bialystok et al 2004Bialystok et al , 2008Costa et al 2008b;Heidlmayr et al 2014Heidlmayr et al , 2015Linck et al 2008), while others did not (Carlson and Meltzoff 2008;Duñabeitia et al 2014; Hilchey and Klein 2011; Humphrey and Valian 2012; Kousaie and Phillips 2012a; Paap and Greenberg 2013; Paap and Sawi 2014). Several studies have highlighted that bilingual individuals have a certain ease to solve conflicts occurring in tasks involving executive control, like the Stroop task (Stroop 1935), the Simon task (Simon and Rudell 1967) or the Tower of Hanoi task (Miyake et al 2000).…”
Section: Bilingualism and Executive Functions Trainingmentioning
confidence: 97%
See 1 more Smart Citation
“…However, results are far from consensual and several studies reported a clear bilingual advantage for performing various tasks involving executive control (e.g. Bialystok et al 2004Bialystok et al , 2008Costa et al 2008b;Heidlmayr et al 2014Heidlmayr et al , 2015Linck et al 2008), while others did not (Carlson and Meltzoff 2008;Duñabeitia et al 2014; Hilchey and Klein 2011; Humphrey and Valian 2012; Kousaie and Phillips 2012a; Paap and Greenberg 2013; Paap and Sawi 2014). Several studies have highlighted that bilingual individuals have a certain ease to solve conflicts occurring in tasks involving executive control, like the Stroop task (Stroop 1935), the Simon task (Simon and Rudell 1967) or the Tower of Hanoi task (Miyake et al 2000).…”
Section: Bilingualism and Executive Functions Trainingmentioning
confidence: 97%
“…The use of more than one language is one of the exercises, amongst other activities such as playing music (Bialystok and DePape 2009), playing computer and video games (Bialystok et al 2006;Dye et al 2009), or practicing sports requiring high level of bimanual coordination (Diamond 2011) that plays a role in the strengthening of executive functions (Bialystok 2001;Bialystok et al 2006;Bialystok and DePape 2009;Costa et al 2008b;Diamond 2010;Heidlmayr et al 2014Heidlmayr et al , 2015Heidlmayr et al , 2016Kroll et al 2012). However, results are far from consensual and several studies reported a clear bilingual advantage for performing various tasks involving executive control (e.g.…”
Section: Bilingualism and Executive Functions Trainingmentioning
confidence: 99%
“…The sustained negative‐going potential, which appears around 550–700 ms after stimulus onset and follows the N450, is believed to index conflict‐resolution and response‐selection processes . Heidlmayr et al . had monolingual and bilingual young adults perform a Stroop task that combined elements of negative priming.…”
Section: Earlier and More Automatic Processes In Bilingualsmentioning
confidence: 99%
“…127 The sustained negative-going potential, which appears around 550-700 ms after stimulus onset and follows the N450, is believed to index conflict-resolution and response-selection processes. 128,129 Heidlmayr et al 130 had monolingual and bilingual young adults perform a Stroop task that combined elements of negative priming. The authors found ERP Stroop effects (incongruent minus congruent) for monolinguals but not bilinguals at both the N450 and the late sustained potential, despite no behavioral differences.…”
Section: N450 and The Late Sustained Negative-going Potentialsmentioning
confidence: 99%
“…second language proficiency, frequency of first and second language use, or the type of interactional context (for a discussion, see [40], but also [37]), which is thought to be related to a differential recruitment of executive control processes [3,4]. As a consequence, different profiles of bilingualism may involve specific sets of control processes.…”
Section: Introductionmentioning
confidence: 99%